Entrustable Professional Activity 10: Recognizing the Acutely Ill Patient-A Delirium Simulated Case for Students in Emergency Medicine - Aaron Dora-Laskey; Harsh Sule; Tiffany Moadel; Nicholas Kman; Laura Thompson; Jamie Hess; Lalena Yarris (Association of American Medical Colleges, 2016)
Abstract Introduction This simulation case was designed to evaluate the ability of third- and fourth-year emergency medicine clerkship students and acting interns to perform the tasks outlined in the Association of American Medical College's Core Entrustable Professional Activity 10, to "recognize a patient requiring urgent or emergent care and initiate evaluation and management." The overarching goal is to assess medical students' ability to recognize and take steps to stabilize a sick patient. Methods In this case, students encounter a physician, simulated with a high-fidelity manikin, who has suddenly become confused. Students are expected to recognize that he is acutely ill, call for help, and begin the initial steps of resuscitation. Bedside testing reveals hypoglycemia, which students are expected to treat. Further examination, history gathering, and diagnostic tests reveal that the patient is suffering from gram-negative sepsis. Students are evaluated on their ability to recognize signs of serious illness, call for appropriate help, perform critical assessment and treatment tasks, communicate their findings to an attending physician, and determine the appropriate patient disposition. Outcomes are measured using critical action checklists. Results Initial trials of this case demonstrated its feasibility. All 13 students who have participated in this session have identified all five critical actions. Discussion In later iterations, the number of roles was streamlined in order to reduce how many personnel were required. As a result of the very high critical-actions success rates of the first two groups of students tested, our case-specific checklist was revised with the goal of improving its discriminatory power.